Examination of benchmarking practices in South Africa firms - Smart, Daniel Arthur John (My University, 2014)
Whilst contemporary managements tore concerned with the measurement of the performance of their businesses, they now recognise that “new strategies and competitive realities demand new measurement systems” (Eccles, 1991). There is a need for management techniques to provide strategic management information as well as operational performance measures. This requires a balance between measuring actions already taken and drivers of future performance (Kaplan & Norton, 1992). In response to the pressures placed on management by market and consumer trends, locally and globally, numerous management techniques have been introduced in an attempt to improve the competitive performance of business in the delivery of products and services to customers (Watson, 1993). Many of these have been oversold as being universally applicable to business whereas they have a limited business application. The net result of this onslaught of techniques is that senior management has become sceptical of those claiming to revolutionise the way to do business. The consequence is that management is reluctant to apply current techniques, but continues to use historical management tools that have been found reliable. One management approach, which continues to be extensively used, is competitive analysis. In the past, this has provided a powerful tool for strategy formulation (Walleck et al, 1991). It has enabled management to determine differences in key quantitative and qualitative measures between the firm and its competitors. The process, however, has only enabled a quantification of th ese competitive gaps in performance. As no analysis of the underlying reasons for the gaps was performed, the result was a management tool that was useful for performance measurement but had limited applications for strategic management. Hence, pure competitive analysis has restricted application as a contemporary management tool. Any management information derived from a competitive analysis would be ascertainable from the application o f a benchmarking process. This is possibly due to benchmarking including, but not being limited to competitor firms as a source of comparisons. Benchmarking is a relatively modem management process that has captured the interest o f business, both as a performance measure and for strategic management. Benchmarking principles are however, not entirely new to business, but are rather a refinement of pure competitive analysis (Mooney, 1995). This view appears to suggest that benchmarking is a natural progression from traditional competitive analysis; an evolution into a superior management tool. Due to benchmarking being a natural progression from competitive analysis, it has comparable conceptual methodologies. These similarities have influenced the acceptance o f benchmarking as a new management tool. The fact that benchmarking at first appears to resemble pure competitive analysis (which most managers are familiar with) has enabled management to identify with benchmarking. The effect is that management is not opposed to implementation of benchmarking programmes (Watson, 1993). It is contended that this is the most important factor responsible for extent of use of benchmarking internationally and the continued growth of benchmarking applications in firms. This link between competitive analysis and benchmarking is further discussed in the next chapter.